Spirituality and communication in health: conceptual basis - Christian de Paul de Barchifontaine (O Mundo da Saúde, 2010)
Interest by the theme of spirituality in work is growing intensely in the last years, especially in the business world. In the course of my reflection, I will use the word enterprise understanding that every health institution is an enterprise. Something formerly seen as a subject restricted to the organizational universe, as something religious or even mystic, is currently inserted as a strategic dimension, because it confers meaning to the mission of the enterprise and to the work of people. Studies show that enterprises that also develop the conscience linked to spirituality make much easier the development of the factors executives most want employees to achieve: motivation, performance, team spirit, efficient communication, quality, and focus in the client, in sum, “happy about what’s going on one’s own life”. After a brief conceptual panorama we will discuss some of the possible hindrances for the development of business spirituality, globalization for example. Then, focusing the crisis of humanism, we will consider contextualization of spirituality in current enterprises. We will exemplify with the efforts of the government regarding humanization, which is in the last instance the crucial point in communication. Health care is global and not only individualized. There is a system (an enterprise) that must be humanized by communication, by conviviality, and it must develop material resources and train people so that that happens.